2018
DOI: 10.31223/osf.io/653cv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cyclic CO2 – H2O injection and residual trapping: implications for CO2 injection efficiency and storage security

Abstract: To meet the Paris Agreement target of limiting global warming to 2ºC or below it is widely accepted that Carbon Capture and Storage (CCS) will have to be deployed at scale. The influence of residual trapping on CO2 well injectivity and its response over time has a major impact on the injection efficiency and storage capacity of CO2 storage sites. For the first time, experiments have been undertaken over six cycles of water and supercritical CO2 injection using a state of the art high flow rig recreating in-sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Of various injection strategies for GCS, cyclic CO 2 -brine injection has drawn significant interest from researchers in the related area for improving residual trapping by alternatively injecting CO 2 with water [14][15][16][17][18][19][20][21][22]. Despite technical difficulties in extracting and discharging a significant amount of brine from deep targeting reservoirs, the use of cyclic CO 2brine injection has been proposed as an effective strategy for mitigating possible risks of leakage by dispersing CO 2 as continuous streams into innumerable tiny blobs and inducing residual trapping which can limit upward mobility and facilitate dissolution of free-phase CO 2 [9,22]. For investigating the effects of cyclic or sequential injection of CO 2 with brine for GCS operations, Saeedi et al [15] conducted coreflooding experiments for sandstone samples with different permeabilities and porosities through nuclear magnetic resonance during seven injection cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of various injection strategies for GCS, cyclic CO 2 -brine injection has drawn significant interest from researchers in the related area for improving residual trapping by alternatively injecting CO 2 with water [14][15][16][17][18][19][20][21][22]. Despite technical difficulties in extracting and discharging a significant amount of brine from deep targeting reservoirs, the use of cyclic CO 2brine injection has been proposed as an effective strategy for mitigating possible risks of leakage by dispersing CO 2 as continuous streams into innumerable tiny blobs and inducing residual trapping which can limit upward mobility and facilitate dissolution of free-phase CO 2 [9,22]. For investigating the effects of cyclic or sequential injection of CO 2 with brine for GCS operations, Saeedi et al [15] conducted coreflooding experiments for sandstone samples with different permeabilities and porosities through nuclear magnetic resonance during seven injection cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Malekzadeh et al [20] developed an analytical solution for a mathematical model describing saturation distribution in a drainage-imbibition process. Edlmann et al [22] presented the results of six cycles of CO 2 -brine injection on injectivity through observations and modeling. In addition, many researchers and engineers in the area of petroleum engineering also conducted experiments and mathematical modeling on use of cyclic injection of CO 2 for increasing capillary trapping and recovery efficiency in EOR operations [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of cyclic injection regimes, which are also known as water alternating gas injection, have mostly been concerned with oil‐gas‐water systems in the context of enhanced recovery (Oak, ; Suicmez et al, ). However, there are several examples of cyclical injection regimes for enhancing CO 2 capillary trapping (e.g., Edlmann et al, ; Herring et al, ; Ruprecht et al, ; Saeedi et al, ), which all indicate that the total amount of CO 2 trapped increases under such an injection regime. This was also the case observed in the current study, with each injection cycle leading to a greater volume of trapped CO 2 , as shown by the increasing residual nonwetting phase saturation in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous experimental studies have measured capillary trapping of CO 2 in rock cores (e.g., Angerer et al, ; Iglauer et al, ; Krevor et al, ; Ni et al, ; Niu et al, ; Pentland et al, ); several have also identified water alternating gas injection (Edlmann et al, ; Herring et al, ; Saeedi et al, ) and injection of foaming agents (Adebayo, ) as viable methods that increase the volume of capillary trapped CO 2 . Although the wettability of CO 2 is a critical factor controlling capillarity in such experiments, the assessment of CO 2 wettability under core flooding conditions remains an experimental challenge.…”
Section: Introductionmentioning
confidence: 99%
“…A share of the hydrogen, often referred to as cushion gas, will remain in the reservoir as a precaution to maintain an operational pressure and to minimise subsurface water encroachment into the working reservoir during withdrawal periods. Additionally, hydrogen will be lost due to a process defined as residual trapping in CO2 storage research [25][26][27] . Small isolated hydrogen bubbles will remain in the pores and cannot be removed; these are residually trapped.…”
Section: Hydrogen Storage In Subsurface Porous Mediamentioning
confidence: 99%